the Influence of Patient Experience and Patient Trust on the Desire to Return to Treatment at the Calysta Karawang Clinic Based on Sor Theory - Rillawanti Yuniar; A. Rohendi; R. Oke Andikarya (Research of Service Administration Health and Sains Healthys, 2025)
Quality health services are one of the main factors in determining patient loyalty, especially in aesthetic clinic services such as the Calysta Karawang Clinic. Patients' experience while receiving services and their level of trust in the clinic are important elements that influence the decision to return for treatment. This study aims to analyze the influence of patient experience and patient trust on the desire to return to treatment using the Stimulus-Organism-Response (SOR) theoretical framework. The research was conducted with a quantitative approach using survey techniques on 81 respondents. The independent variables studied were patient experience (X₁) and patient trust (X₂), while the dependent variable was the desire to return (Y). Data analysis was carried out with multiple linear regression using SPSS 26. The results showed that both partially and simultaneously, patient experience and patient trust had a significant effect on the desire to return to treatment. The coefficient of determination (R²) of 83.7% indicates that the two variables are able to explain the variation in the desire to return strongly. The findings emphasize the importance of improving doctor-patient communication, facility convenience, cost transparency, and strengthening clinic image to increase patient loyalty.